Social media brand engagement in the context of collaborative consumption: the case of AIRBNB - Schivinski, B.; Langaro, D.; Fernandes, T.; Guzmán, F. (Journal of Brand Management, 2020)
This study focuses on social media brand engagement in the context of shared and collaborative consumption businesses, a novel trend in the hospitality industry. By drawing on the concept of brands being defined collectively through an assemblage of heterogonous human and nonhuman actors, and focusing on the brand Airbnb—a peer-to-peer online platform for renting, swapping, and lending accommodations—the current study examines how consumers’ perceptions of Airbnb brand equity mediate the relationship between functional and hedonic brand image and social media behavioral engagement in terms of consumption, contribution, and creation of brand-related content (COBRAs). Results discriminate between direct and indirect effects. Findings reveal that hedonic brand image directly influences behavioral engagement on social media, whereas brand equity fully mediates the relationship between functional brand image and COBRAs. Implications for theory and practice related to shared or collaborative consumption platforms in the hospitality industry are discussed and suggestions for future studies are presented. This research paper provides conceptual and theoretical clarity on issues such as how consumers’ brand perceptions influence their behavioral engagement on social media.